Staphylococcal Colonisation of Intravenous Cannula and Antimicrobial Patterns of Isolated Staphylococcus Species - Mahto, R; Amatya, J; Amatya, R; Adhikari, D (Nepal Journal of Science and Technology, 2014)
Cannula-related infections are amongst the most important nosocomial infections. Staphylococcus aureus and coagulase negative Staphylococci (CONS) are the most frequent causes of colonizing the intravenous cannula through which infection may occur. The aim of the study was to isolate the colonized staphylococci and to study the antimicrobial sensitivity pattern against them. Cultures of cannula tips were raised by semi-quantitative method. Antibiotic susceptibility test was performed by Kirby Bauer disc diffusion method as per The Clinical and Laboratory Standard Institute (CLSI) guidelines. Coagulase positive Staphylococcus was confirmed by coagulase slide test followed by tube test. CONS were distinguished by novobiocin sensitivity test. Out of 200 samples of cannula tips collected and processed, 45 (22.5%) isolates were S. aureus, 15 (7.5%) were S. epidermidis and 16 (8%) were other CONS. The highest occurance (30.7%) of S. aureus and the CONS (18.4%) was found in the nephrology ward and the surgical ward respectively. All the 76 isolates were tested for antimicrobial susceptibility pattern. Novobiocin was used to differentiate S. epidermidis from other CONS. All isolates were sensitive to ampicillin and ofloxacin. Out of total, 46.7% isolates of S. aureus and 12.9% isolates of CONS were multidrug resistant; 35.5% and 20 % isolates of S. aureus were oxacillin (methicillin) resistant and vancomycin resistant respectively. Four (12.9%) isolates of CONS [2(13.3%) of other CONS and 2(12.5%) of S. epidermidis] were oxacillin (methicillin) and vancomycin resistant. In our study, vancomycin resistant staphylococci were found and it was concluded that the precautions for inserting intravenous cannula is necessary as different kinds of pathogens may colonize such devices. DOI: http://dx.doi.org/10.3126/njst.v14i2.10426 Nepal Journal of Science and Technology Vol. 14, No. 2 (2013) 131-136